Divergent CD4+ T memory stem cell dynamics in pathogenic and nonpathogenic simian immunodeficiency virus infections - Cartwright, Emily K; McGary, Colleen S; Cervasi, Barbara; Micci, Luca; Lawson, Benton; Elliott, Sarah T C; Collman, Ronald G; Bosinger, Steven E; Paiardini, Mirko; Vanderford, Thomas H; Chahroudi, Ann; Silvestri, Guido (The Journal of immunology (1950), 2014)
Recent studies have identified a subset of memory T cells with stem cell-like properties (T(SCM)) that include increased longevity and proliferative potential. In this study, we examined the dynamics of CD4(+) T(SCM) during pathogenic SIV infection of rhesus macaques (RM) and nonpathogenic SIV infection of sooty mangabeys (SM). Whereas SIV-infected RM show selective numeric preservation of CD4(+) T(SCM), SIV infection induced a complex perturbation of these cells defined by depletion of CD4(+)CCR5(+) T(SCM), increased rates of CD4(+) T(SCM) proliferation, and high levels of direct virus infection. The increased rates of CD4(+) T(SCM) proliferation in SIV-infected RM correlated inversely with the levels of central memory CD4(+) T cells. In contrast, nonpathogenic SIV infection of SM evidenced preservation of both CD4(+) T(SCM) and CD4(+) central memory T cells, with normal levels of CD4(+) T(SCM) proliferation, and lack of selective depletion of CD4(+)CCR5(+) T(SCM). Importantly, SIV DNA was below the detectable limit in CD4(+) T(SCM) from 8 of 10 SIV-infected SM. We propose that increased proliferation and infection of CD4(+) T(SCM) may contribute to the pathogenesis of SIV infection in RM.